Metabolomic profile of cerebral tissue after acoustically-mediated blood-brain barrier opening in a healthy rat model: a focus on the contralateral side - Presset, Antoine; Bodard, Sylvie; Lefèvre, Antoine; Millet, Anaïs; Oujagir, Edward; Dupuy, Camille; Iazourène, Tarik; Bouakaz, Ayache; Emond, Patrick; Escoffre, Jean-Michel; Nadal-Desbarats, Lydie (Frontiers in Molecular Neuroscience, 2024)
Microbubble (MB)-assisted ultrasound (US) is an innovative modality for the non-invasive, targeted, and efficient delivery of therapeutic molecules into the brain. Previously, we reported the first metabolomic signature of blood–brain barrier opening (BBBO) induced by MB-assisted US. In the present study, the neurometabolic consequences of acoustically-mediated BBBO on cerebral tissue were investigated using multimodal metabolomics approaches. Sinusoid US waves (1 MHz, peak negative pressure 0.6 MPa, burst length 10 ms, total treatment time 30 s, MB bolus dose 0.7 × 105 MBs/g) were applied on the rats’ right striatum (ipsilateral side). Brain was collected and both striata were then dissected 3 h, 2 days, and 1 week after BBBO. After tissue preparation, the samples were analyzed using nuclear magnetic resonance spectrometry (NMRS) and high-performance liquid chromatography coupled to mass spectrometry (HPLC-MS). Our findings showed a slight disruption of metabolic pathways in contralateral striata of animals. Analyses of metabolic pathways indicated changes in amino acid metabolisms. In addition, tryptophan derivate dosages revealed the perturbation of a central metabolite of the kynurenine pathway (i.e., 3-hydroxy-kynurenine). In conclusion, the acoustically-mediated BBBO of the ipsilateral cerebral hemisphere induced significant change in metabolism of contralateral one.